The mitochondrial DNA HVI and HVII sequences and haplogroup distribution in a population sample from Vietnam - Nam Ngoc Nguyen; Trong Luc Hoang; Trang Hong Nguyen; Phuong Thi Le; Chi Hung Nguyen; Viet Vinh Tran; Hoang Ha Chu; Ha Hoang (Taylor & Francis Group, 2022)
Background Mitochondrial DNA (mtDNA) analysis has been used in forensics and requires well-established population databases for statistical interpretations. However, high-quality mtDNA data from Vietnamese population samples have been limited. Aim To examine the mtDNA sequences and haplogroup compositions of a Vietnamese population to provide an mtDNA dataset that can further be used to construct a Vietnamese-specific reference database. Subjects and methods A total of 173 Vietnamese individuals were analysed for two hypervariable regions (HVI and HVII) of mtDNA. Forensic parameters were calculated and haplogroup assignment was performed based on the resulting mtDNA haplotypes. Genetic relationships between the Vietnamese and other Asian populations were investigated through principal component analysis (PCA) and pairwise Fst. Results The Vietnamese population sample consisted of 145 different haplotypes with a random match probability of 0.96%, a power of discrimination of 0.9904, and a haplotype diversity of 0.9962. The samples were assigned to 83 haplogroups that were commonly reported in Asia. PCA and pairwise Fst revealed close relationships of the Vietnamese population with other Asian populations, especially with populations in proximity. Conclusion The results from this study can contribute to the current genetic information content as a supplementary mtDNA reference dataset for forensic investigations and phylogenetic research.